205. IL-1 β gene (+3954C/T, exon 5, rs1143634) and NOS2 (exon 22) polymorphisms associate with early aseptic loosening of hip and knee arthroplasties but not with implants infection. (15th December 2022) - Lopez-Anglada, Esteban; Collazos, Julio; Montes, Angel Hugo; Perez-Is, Laura; Perez-Hevia, Imanol; Jimenez-Tostado, Sergio; Suarez-Zarracina, Tomas; Alvarez, Victoria; Valle-Garay, Eulalia; Asensi, Victor
Abstract: Background: Aseptic prosthetic loosening (APL) and prosthetic joint infections (PJI) are frequent complications of hip and knee implants. Polymorphisms of cytokines and nitric oxide (NO), key inflammatory molecules in APL and PJI pathogenesis, could explain individual susceptibility to these complications. Methods: Three cytokines ( IL-1-a, IL-1-β, TNF-α) and two nitric oxide synthase ( NOS2, NOS3 ) genes polymorphisms were genotyped in 77 APL and 117 PJI patients and 145 controls with aseptic hip or knee implants lasting > 16 years. Plasma cytokines and nitrate-nitrite (NOx) levels were measured. Results: The TT genotype and T allele of the (+3954C/T, exon 5, rs1143634) IL-1β polymorphism were more frequent in APL patients compared to controls (p=0.03 and p=0.02, respectively). No genotypic associations in PJI patients were observed. S. epidermidis was their most frequently isolated microorganism (39.3%). Plasma IL-6, TNF-α and NOx were significantly different between APL and controls (p< 0.0001). Plasma IL-1β and IL-6 were significantly higher in APL T allele carriers vs. non-carriers (p< 0.03). Knee implant (HR 2.488, 95% CI 1.307-4.739, p=0.005), male gender (HR 2.252, 95% CI 1.121-4.525, p=0.023), carriages of the TT genotype of the (+3954C/T) IL-1β polymorphism (HR 3.704, 95% CI 1.274-10.753, p=0.016) and AA genotype of the (exon 22) NOS2 polymorphism (HR 3.509, 95% CI 1.266-9.709, p=0.016) were independently associated with a shorter implant survival by Cox regression. Conclusion: Genotyping of IL-1β (+3954C/T, exon 5, rs1143634 ) and NOS2 (exon 22) polymorphisms could be useful as predictors of early hip or knee APL. Disclosures: All Authors : No reported disclosures.